The Commitment Of The Human Cell Atlas To Humanity - Awandare, G.; Arzuaga, F.; Ardlie, K.; Amit, I.; et al. (Nature Communications, 2024)
The Human Cell Atlas (HCA) is a global partnership “to create comprehensive reference maps of all human cells—the fundamental units of life – as a basis for both understanding human health and diagnosing, monitoring, and treating disease.” (https://www.humancellatlas.org/) The atlas shall characterize cells from diverse individuals across the globe to better understand human biology. HCA proactively considers the priorities of, and benefits accrued to, contributing communities. Here, we lay out principles and action items that have been adopted to affirm HCA’s commitment to equity so that the atlas is beneficial to all of humanity.
Research Article
Keywords: Atlas; Humanity; Human Cell Atlas